Physical therapy case files. - Brumitt, Jason (McGraw-Hill Medical, 2013)
Gives you case studies that illustrate critical concepts you need to build and enhance your skills in orthopaedic physical therapy. This title features each case that includes a discussion of the health condition, examination, evaluation, diagnosis, plan of care and interventions, evidence-based practice recommendations, and references.